1991
DOI: 10.1073/pnas.88.2.598
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of protein kinase C beta 1 enhances phospholipase D activity and diacylglycerol formation in phorbol ester-stimulated rat fibroblasts.

Abstract: We are using a Rat-6 fibroblast cell line that stably overexpresses the P1 isozyme of protein kinase C (PKC)to study regulation of phospholipid hydrolysis by PKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…First, PKC may directly regulate PLD activity by phosphorylation, as suggested by enhanced phorbol ester stimulation of PLD in R6-PKC3 fibroblasts (Pai et al, 1991). In support of this, MacNulty et aL (1990) found that ETstimulated choline release was abolished on PKC down-regulation.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…First, PKC may directly regulate PLD activity by phosphorylation, as suggested by enhanced phorbol ester stimulation of PLD in R6-PKC3 fibroblasts (Pai et al, 1991). In support of this, MacNulty et aL (1990) found that ETstimulated choline release was abolished on PKC down-regulation.…”
Section: Discussionmentioning
confidence: 55%
“…As we proposed previously (Pai et al, 1991), enhanced PLD activity can generate an enhanced DAG signal by the PLD-PA phosphohydrolase pathway, and this DAG may lead to further PKC activation, thus perpetuating the signal through a feed-forward loop of cell stimulation (Pai et al, 1991). A role for sustained DAG formation in the mitogenic response of fibroblasts has previously been suggested (Muldoon et aL, 1990;Wright et aL, 1990 (Martin et al, 1990;Leach et al, 1991) argue against such a model.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations